EKSISTENSI BUDAYA SENI TARI JAWA DI TENGAH PERKEMBANGAN MASYARAKAT KOTA SEMARANG (Forum Ilmu Sosial, 2013)
Culture heritage variety that Indonsia has is a nation identity. This Culture heritage was not getting note when there was an identity crisis. This situation has been show with a lot of claim cases of Indonesian arts and culture by neighbor countries. The positive effect from these cases is growt community spirit to conserve Indonesian culture. One of the efforts that community can do in conserve Java culture is like the citizen in Sampangan village Gajahmungkur sub district Semarang City. Participaton in conserve the Javanese art dances is such as with pay the Javanese dance course, pick up children that join in this course. Involvement of citizen in conserve this art is because of a few factor suh as interested in javanesse puppet and also javanese culture for adult, children that has interesting showing in television adn being watched by their friend. The obstacle of this conserve is from the performance such as children are not seriously in practice even when they felt bored. This is the obstacle that must management, dance teacher faces.